DIFFERENCES IN PARENTS' KNOWLEDGE REGARDING ARI PREVENTION IN TOddlers ON THE GROUPS THAT ARE PROVIDED POCKET BOOK AND THE GROUP THAT IS PROVIDED BY LEAFLET - Wijayanti, Ika (Jurnal Medicare, 2022)
ARI in toddlers is very dangerous if not treated immediately, it is necessary to increase knowledge by providing education on how to prevent ARI in toddlers. Pocket Book Media is a tool in the form of a book, equipped with writing and pictures that can cover many people, practical in its use because it can be used anywhere. Media leaflet is a sheet of paper that contains writing in short, dense, easy-to-understand sentences and simple pictures. The aim of the study was to determine whether there was a difference in parental knowledge about preventing ARI in toddlers against the group given pocket books and the group given leaflets. This research method uses a quasi-experimental approach with a two group pretest – posttest design approach. The population in this study were children under five who suffered from ARI in January-February 2021 in the Hebeybhulu Yoka Health Center area totaling 56 people, while the sample using random sampling technique was 30 people. The data collection instrument used a questionnaire. The results showed that there was no difference in parental knowledge about ARI prevention in the group given the Pocket Book and the group given Leaflets.